Topological edge properties of C60+12n fullerenes - Mottaghi, A.; Ashrafi, Ali R. (Beilstein Journal of Nanotechnology, 2013)
A molecular graph M is a simple graph in which atoms and chemical bonds are the vertices and edges of M, respectively. The molecular graph M is called a fullerene graph, if M is the molecular graph of a fullerene molecule. It is well-known that such molecules exist for even integers n ≥ 24 or n = 20. The aim of this paper is to investigate the topological properties of a class of fullerene molecules containing 60 + 12n carbon atoms.
Keywords: edge revised Szeged index; edge Szeged index; edge topological property; fullerene; PI index